Web-Based Management Information System Design for Departmental Student Association Activities - Siti Ilmiyah; Nur Cahyo (International Journal of Information Systems and Technology, 2026)
The Information Technology Student Association (HMJ) at UIN XYZ is a vital organization for coordinating student aspirations and activities; however, its effectiveness is often hindered by fragmented, manual administrative management. This study aims to design and implement a web-based activity management information system capable of efficiently centralizing operational data. The system was developed using the Waterfall Software Development Life Cycle (SDLC) model, encompassing the stages of Requirement Analysis, System Design, Implementation, and Integration and System Testing. Key technologies employed include the PHP programming language with the CodeIgniter 3 framework and the MySQL database management system. Functional testing via Black Box Testing demonstrated that all features operated according to specifications, while User Acceptance Testing (UAT) yielded an average score of 92%. Based on this result, the system is categorized as "Highly Suitable" for implementation as a digital solution to enhance the organization's financial transparency and administrative orderliness.